Foreign body aspirations in children- it is a single center experience (Annals of Medical Research, 2021)
Aim: Foreign body aspiration causes serious mortality in children and is an important emergency condition requiring early diagnosis and bronchoscopy in the childhood period. In our research, we evaluated data from cases treated with the diagnosis of foreign body aspiration within 9 years in our clinic in terms of the complications during and after the procedures. This study aimed to determine the demographic and clinical characteristics of patients admitted for foreign body aspiration, to evaluate bronchoscopy findings, and to compare early and late-diagnosed patients.Material and Methods: The files of cases that underwent bronchoscopy for a suspected foreign body aspiration in our hospital from January 2010 to September 2019 were investigated retrospectively. A total of 54 children were evaluated. All the bronchoscopies were performed with general anesthesia. The patients were evaluated in terms of clinical and examination findings, radiological findings, and complications that developed during and after anesthesia.Results: Of all the patients, 63% were boys. The most common findings on admission were cough in 96.3% and respiratory problems in 33.3%. Of all the patients, 40.7% had reduced respiratory sounds on the right and 44.4% had foreign objects removed from the right main bronchus. The most commonly aspirated object was walnut. During anesthesia, the most commonly observed complication was low saturation, and laryngeal edema was most common after anesthesia.Conclusion: Rapid and systematic evaluation and referral to a center with bronchoscopy experience are considered life-saving factors for children with a suspected aspiration of a foreign body.
Keywords: Foreign body; aspiration; children; bronchoscopy